Autonomous Robot Project Based on the Robot Operating System Platform - Szymon CHERUBIN (Projekt robota autonomicznego bazującego na platformie Robot Operating System, 2022)
This article presents the concept of an autonomous mobile robot running on the ROS system and using advanced algorithms for 2D map generation and autonomous navigation. The authors focused on presenting the hardware platform, the Linux-based software and the Robot Operating System (ROS) platform. This article also introduces an algorithm that provides the generation of a 2D map of the surroundings, autonomous robot driving and remote control of the device. Measurements of the temperature of the computer helped in the decision on which cooling system to use.
Keywords: Projekt robota autonomicznego